Pharmacological effects and molecular mechanisms of action of a herbal medicine based on Vitex agnus-castus - I. V. Vysotskaya; V. P. Letyagin (ABV-press, 2017)
Dyshormonal breast dysplasia is the most frequent pathology encountered by practitioners. The interest of clinicians to these processes is associated with several factors. On the one hand effective treatment, relieves symptoms, ensures the quality of life. On the other hand, mastitis is a risk factor for subsequent malignant tumor. Therefore, timely correction is a variant of primary prevention of breast cancer. The choice of the adequate tactics of conducting such patients from the existing diversity of dosage forms is the key to success. The paper discusses the main molecular mechanisms that are implemented with the use of the drug Mastodynon.